2019
DOI: 10.3390/ijms20215436
|View full text |Cite
|
Sign up to set email alerts
|

The Systemic Immune Response to Collagen-Induced Arthritis and the Impact of Bone Injury in Inflammatory Conditions

Abstract: Rheumatoid arthritis (RA) is a systemic disease that affects the osteoarticular system, associated with bone fragility and increased risk of fractures. Herein, we aimed to characterize the systemic impact of the rat collagen-induced arthritis (CIA) model and explore its combination with femoral bone defect (FD). The impact of CIA on endogenous mesenchymal stem/stromal cells (MSC) was also investigated. CIA induction led to enlarged, more proliferative, spleen and draining lymph nodes, with altered proportion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Previous work, in a femoral bone injury model, showed a reduction in proportions of myeloid cells and activated myeloid cells, in BL, SP and LN, accompanied by increased T cells, but decreased activated T cells, 6 days after femoral bone injury (end of acute inflammation stage), in animals that progressed faster towards bone repair [14]. On the other hand, in a model of chronic inflammation, Collagen-Induced Arthritis (CIA), the proportion of activated myeloid cells was increased in SP 3 days after femoral bone injury [40]. These changes in cell proportions will be influenced by the specificities of the models and the time postinjury of the analysis, and in these studies, the local immune cell presence was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work, in a femoral bone injury model, showed a reduction in proportions of myeloid cells and activated myeloid cells, in BL, SP and LN, accompanied by increased T cells, but decreased activated T cells, 6 days after femoral bone injury (end of acute inflammation stage), in animals that progressed faster towards bone repair [14]. On the other hand, in a model of chronic inflammation, Collagen-Induced Arthritis (CIA), the proportion of activated myeloid cells was increased in SP 3 days after femoral bone injury [40]. These changes in cell proportions will be influenced by the specificities of the models and the time postinjury of the analysis, and in these studies, the local immune cell presence was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the presence of myeloid cells (CD11b/c + ) was significantly higher in the blood when compared to the control. Interestingly, the amount of T lymphocytes was significantly decreased in lymph nodes, whereas natural killer cells (NK) were increased in the spleen (Teixeira et al, 2019). This report also showed that the proportions of CD8 + and CD4 + T cells were similar between all animals in the blood and spleen; however, the presence of CD4 + T lymphocytes was decreased in the lymph nodes compared to the control (Teixeira et al, 2019).…”
Section: Similaritiesmentioning
confidence: 51%
“…Interestingly, the amount of T lymphocytes was significantly decreased in lymph nodes, whereas natural killer cells (NK) were increased in the spleen (Teixeira et al, 2019). This report also showed that the proportions of CD8 + and CD4 + T cells were similar between all animals in the blood and spleen; however, the presence of CD4 + T lymphocytes was decreased in the lymph nodes compared to the control (Teixeira et al, 2019). Various leukocytes migrated to the inflamed ankle tissue and increased expression of adhesive molecules and chemokines, which progressed into intensified production of chemokines and pro-inflammatory and anti-inflammatory cytokines (Nevius et al, 2016).…”
Section: Similaritiesmentioning
confidence: 99%
“…Van Esch et al [17] in the 2001 described as iperactivation of T-cells, through the reticulation of B-cells mediated by CD40, it is at the same time responsible of the sistemyc chemotaxis of eosinophils and production of RF. Most recently, it is demonstrated that the role of some interleukines (IL6,IL1,IL10; IL5,IL4 and IL12 in mouse model CIA) ( 24) and Chemokines (eotaxin 1 and 2) induce the recruitment of eosinophils by macrophages and limphocites T and inhibit apopthosis of eosinophilic in ltrates in tissues.…”
Section: Discussionmentioning
confidence: 99%